Pengetahuan Remaja Putri Kelurahan Langensari RT 15 RW 05 Tentang Pijat Akupresur Mengurangi Nyeri Haid - Bernadeta Ngole; Masruroh; Nurul Qomariah (Universitas Ngudi Waluyo, 2022)
Family study practice (PPK) is one of the student activities that must be carried out where it is a real form of work in providing Community Midwifery Care Services, where community midwifery is one of the courses in the Community Midwifery Profession curriculum with the aim of implementing comprehensive Midwifery practice by paying attention to culture. society in a community setting with a midwifery management approach and based on the concept of professional skills and attitudes. After following the Family Study Practice (PPK) students are expected to be able to identify, plan, prioritize, implement, and evaluate the management of community midwifery services with community movement and empowerment techniques and educational approaches to individuals, families, special groups or in certain communities in achieving the SDGs. In the implementation of this community midwifery practice, the assessment was carried out by means of direct interviews, and secondary data collection. After being given information and education counseling (IEC) about acupressure massage, the results of 15 questionnaire questions about acupressure massage to reduce menstrual pain adolescents were able to answer correctly on each question as much as 83%-100% correct. Young women already know how to deal with menstrual pain with non-pharmacological therapy in the form of acupressure massage. AbstrakPraktik pengkajan Keluarga (PPK) merupakan salah satu kegiatan mahasiswa yang harus dilaksanakan dimana suatu bentuk kerja nyata dalam memberikan Pelayanan Asuhan Kebidanan Komunitas, dimana kebidanan komunitas ini merupakan salah satu mata kuliah dalam kurikulum Profesi Kebidanan Komunitas dengan tujuan melaksanankan praktik Kebidanan secara komperehensif dengan memperhatikan budaya masyarakat dalam tatanan di Komunitas dengan pendekatan manajement kebidanan dan didasari oleh konsep keterampilan dan sikap Profesional. Setelah mengikuti Praktik pengkajan Keluarga (PPK) diharapkan mahasiswa mampu mengidentifikasi, merencanakan, memprioritaskan, mengimplementasikan, dan mengevaluasi manajement pelayanan kebidanan komunitas dengan teknik pergerakan dan pemberdayaan masyarakat serta pendekatan edukasi pada individu, keluarga, kelompok khusus ataupun pada komunitas tertentu dalam mencapai SDG’s. Dalam pelaksanaan praktik kebidanan komunitas ini pengkajian dilakukan dengan cara wawancara langsung, dan pengambilan data sekunder. Setelah diberikan konseling informasi dan edukasi (KIE) tentang pemijatan akupresur diperoleh hasil dari 15 soal kuesioner tentang pijat akupresur untuk mengurangi nyeri haid remaja mampu menjawab benar pada setiap soal sebanyak 83%-100% benar Remaja putri sudah mengetahui cara untuk mengatasi nyeri haid dengan terapi non farmakologi berupa pijat akupresur.